Management of a Recurrent Pyogenic Granuloma of the Hard Palate with Diode Laser: A Case Report - Hasanoglu Erbasar, Güzin Neda; Senguven, Burcu; Gultekin, Sibel Elif; Cetiner, Sedat (Journal of Lasers in Medical Sciences, 2016)
Introduction: Pyogenic granuloma (PG) is a prevalent inflammatory hyperplasia of skin and oral mucosa which is often caused by constant low-grade local irritation, traumatic injury or hormonal factors. In many cases, gingival irritation and inflammation due to poor oral hygiene are precipitating factors. Oral PG occurs predominantly on the gingiva, but it is also encountered on the lips, tongue, buccal mucosa and rarely on the hard palate. Although surgical excision is the first choice of treatment, many other treatment modalities could be counted such as cryosurgery, sodium tetradecyl sulfate sclerotherapy, intralesional steroids, flash lamp pulsed dye laser, neodymium-doped yttrium aluminium garnet (Nd:YAG) laser, carbon dioxide (CO2) laser, erbium-doped yttrium aluminum garnet (Er:YAG) lasers and diode laser have been suggested. After surgical excision recurrence occurs up to 16% of these lesions. It is believed that recurrence ensues as a result of incomplete excision, failure to eliminate etiologic factors or repeated trauma. Case Report: A 50-year-old female was referred to the Department of Oral Surgery, Gazi University, School of Dentistry, complaining of a swelling and growth on the right side of the hard palate for four months. Patient reported a similar growth in the same area about two years earlier, which had turned out to be a PG by histopathology. The treatment plan included surgical excision of the lesion using diode laser. Results: The patient reported no pain after the surgery. She was discharged with a prescription of chlorhexidine mouthwash and necessary post-operative instructions. At 7 days follow up visit, immediate recurrence of the lesion was observed, and it was excised by diode laser with 2 mm margins at its clinical periphery, to a depth up to the periosteum, by the same operator. No recurrence or scarring was observed in 14 months follow-up. Conclusion: Although diode laser is a secure and efficient technique for the treatment of intraoral PG, in order to minimize its recurrence, the lesion should be excised with a wider margin down to the periosteum or to the causing agent. Also due to its high recurrence rate, long-term follow-up is recommended.